Congo bands of Barra do Jucu: memory, actions and meanings in the Feast of Saint Benedict - Macedo, Inara Novaes (Revista do Colóquio, 2022)
The congo of Espírito Santo is a popular manifestation that has forms of expression and symbolic elements associated with religiosity and daily life, transmitted orally from generation to generation. This practice has a strong influence on the constitution and representation of the local identity of communities that have traditional groups. São Benedito is the patron saint of the congo bands and the planting of the mast is a ritual that celebrates devotion to him, while also establishing a symbolic interaction between the environment and the subjects participating in the celebration. This work aims to analyze the ritual of the planting of the mast of São Benedito in the community of Barra do Jucu, Vila Velha - ES. ​​Based on the description of actions, visual elements and trajectories of the congo bands, we seek to understand the symbolism, memory and meanings of this practice.